The sea urchin embryo and the cell stress responses: new perspectives - Deidda, Irene; Russo, Roberta; Lampiasi, Nadia; Zito, Francesca; Bonaventura, Rosa (Frontiers in Cell Death, 2024)
In addition to many industrial activities that release pollutants in coastal areas, numerous human behaviors contribute to climate change, inducing global warming as well, which can also reshape the environmental impacts of some pollutants. Therefore, it is extremely important to develop new tools that can detect pollutants and environmental changes quickly and easily, but at the same time with high levels of sensitivity. The sea urchin embryo is a well-known model used worldwide in many research fields, including marine ecotoxicology, as a huge range of contaminants can affect its embryonic development with species-specific sensitivity. Morphological abnormalities are already considered biomarkers to evaluate the effects of pollutants and, indeed, the sea urchin has long been used as one of the key species in a battery of bioassays to assess the toxicity of many pollutants and dredged sediments. At a cellular level, the molecular mechanisms activated against a stress agent constitutes what is known as the “cell stress response”, analyzed here within a whole organism, namely the sea urchin embryo. In this minireview, we have reported the available molecular biomarkers linked to morphological abnormalities, as well as the genes affected by environmental changes and emerging pollutants, highlighting those studies that use high-throughput screening approaches to evaluate the effects of environmental conditions on sea urchin embryos.